IMPLEMENTASI PRINSIP KESANTUNAN BAHASA PADA IKLAN PRODUK LIFEBOUY - Domas Sugrahita Harja Susetya; Safira Hamdala; Moh. Fajar Al Hakim (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2022)
This study discusses language politeness in Lifebuoy product advertisements based onLeech's theory. The type of research conducted is qualitative research. The data sourcecomes from Lifebuoy advertisements. The research data is in the form of speech/speechcontaining the politeness of the language spoken by the Lifebuoy advertising actor. Thedata collection method is qualitative and descriptive with listening, recording, and notetaking techniques. After the research data were found and recorded, the researchers conducted data analysis. The analysis technique used by the researcher is data reduction, data display, and conclusion. The results showed that there were six principles of politeness in language, namely the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of simplicity, the maxim of consensus, and the maxim of sympathy.